2015
DOI: 10.1371/journal.pone.0138943
|View full text |Cite
|
Sign up to set email alerts
|

Canine CNGA3 Gene Mutations Provide Novel Insights into Human Achromatopsia-Associated Channelopathies and Treatment

Abstract: Cyclic nucleotide-gated (CNG) ion channels are key mediators underlying signal transduction in retinal and olfactory receptors. Genetic defects in CNGA3 and CNGB3, encoding two structurally related subunits of cone CNG channels, lead to achromatopsia (ACHM). ACHM is a congenital, autosomal recessive retinal disorder that manifests by cone photoreceptor dysfunction, severely reduced visual acuity, impaired or complete color blindness and photophobia. Here, we report the first canine models for CNGA3-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 73 publications
(98 reference statements)
0
28
0
Order By: Relevance
“…These models represent bona fide human disease homologues where the disease phenotype in model and man are the same. Selected examples include RPE65 -LCA, 3 , 5 , 29 BEST1 -BVMD, 30 – 32 CNGB3 - and CNGA3 -achromatopsia, 33 , 34 RHO -ADRP, 35 RPGR -XLRP, 32 , 36 – 38 and NPHP5 -LCA. 39 …”
Section: Animal Modelsmentioning
confidence: 99%
“…These models represent bona fide human disease homologues where the disease phenotype in model and man are the same. Selected examples include RPE65 -LCA, 3 , 5 , 29 BEST1 -BVMD, 30 – 32 CNGB3 - and CNGA3 -achromatopsia, 33 , 34 RHO -ADRP, 35 RPGR -XLRP, 32 , 36 – 38 and NPHP5 -LCA. 39 …”
Section: Animal Modelsmentioning
confidence: 99%
“…Protein modeling of the canine R424W mutation found the disruption of this salt bridge plays an important role in protein folding, subunit assembly and channel gating. In vitro expression studies of the R424W mutation showed increased mislocalization of the mutant CNGA3 protein and the mutant channels did not produce cyclic nucleotide-activated currents [82].…”
Section: Cnga3mentioning
confidence: 96%
“…The mutations, p.Arg424Trp and p.Val644del (R424W and V644del, respectively), provided intriguing mutation sites for in vitro testing. Modeling of these mutations lead to further insights into CNG channel gating and subunit interactions [82]. The residue R424 is located in the S6 transmembrane helix and forms a salt bridge with the residue E306 in the S4-S5 linker.…”
Section: Cnga3mentioning
confidence: 99%
See 1 more Smart Citation
“…For selected canine breeds, the diagnosis of cd is aided by genetic tests. As far as the aetiology of cd is concerned, CNGA3 (Cyclic Nucleotide Gated Channel Alpha 3) gene mutation in German Shepherd (R424W mutation) and Labrador Retriever (V644del mutation) (Tanaka et al, 2015), CNGB3 (Cyclic Nucleotide Gated Channel Beta 3) gene mutations in German Shorthaired Pointers (D262N mutation) (Sidjanin et al, 2002) and CNGB3 gene deletion in Alaskan Malamute (Sidjanin et al, 2002), Miniature Australian Shepherd, Alaskan Sled Dogs and Siberian Husky (Yeh et al, 2013) have been discussed. All these genes mutations are specifically expressed in the cone photoreceptors leading to achromatopsia.…”
mentioning
confidence: 99%